Aspectos motivacionais em praticantes de musculação - Vich Junior, José Roberto [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Over the years, there is a great adherence of individuals to physical activity, which were related to weight training, pilates, gymnastics groups, or any other activity that helps practitioners to achieve a more active and healthy life. Thus, due to this large number of practitioners, which is increasing every year, there is also the large increase of places related to these types of practices, such as gyms, pilates studios, among others. How resistance exercise has been acquiring more and more new fans, it is necessary to highlight the importance of motivation in adherence to physical activity and consequently to improve the quality of life of the individuals. The study aims to investigate what are the predominant motivating factors in practitioners of weight training. For the realization of this work will be used literature review. In this review we will try to search in the literature hall aspects related to motivation, drawing a parallel between the motivational aspects and practitioners of weight train

Com o passar dos anos, nota-se a grande aderência de indivíduos a prática de atividade física, sendo elas relacionadas à musculação, ao pilates, as ginásticas em grupo, ou qualquer outra atividade que auxilie os praticantes a uma vida mais ativa e saudável. Dessa maneira, devido a esse grande número de praticantes, que vem aumentando a cada ano, nota-se também o grande aumento de estabelecimentos relacionados a esses tipos de praticas, como academias de ginástica, estúdios de pilates, entre outros. Onde o exercício resistido vem adquirindo cada vez mais novos adeptos, diante disso é necessário destacar a importância da motivação na adesão a prática de atividade física e, consequentemente, na melhora da qualidade de vida dos indivíduos. O trabalho tem como objetivo investigar, quais são os fatores motivacionais predominantes em praticantes de musculação. Para a realização desse trabalho, será utilizada revisão bibliográfica. Nessa revisão, tentaremos buscar na literatura aspectos relacionados à motivação, traçando um paralelo entre os aspectos motivacionais e os praticantes de musculação
Keywords: Musculação; Esportes - Aspectos psicológicos; Motivação (Psicologia); Qualidade de vida